A questão identitária dos portadores de HIV em Alvorada entre a modernidade e a pós-modernidade - Fonseca, Antônio César Santos (Universidade do Vale do Rio dos Sinos, 2016)
This master thesis investigates the processes that are linked to identity issue of HIV/AIDS in the city of Alvorada – RS, during the widespread crisis of the modern paradigm, identified as the project of modernity, which was basead on a vision rationalist, and another post-modern bias, at which time the person living with HIV/AIDS is no stigmatized as “person living with AIDS”. The research grounded through the theoretical perspective of Stuart Hall, wich provides a discussion of the concept of “decentered subject”. We believe that this concept contributes to a reflection of the changes and the complexity of the modern world and particularly of people living with HIV/AIDS. The methodological of procedures proposed for its preparation have the modality of qualitative research, and as data collection techniques are used semi-strutured interviews, the field diary and participant observation. We believe that the person with HIV/AIDS today, experiencing new identities, no longer linked to the previous stigma of “person with AIDS”.
Keywords: AIDS; Modernidade; Pós-modernidade; Sociologia; Cotidiano; Modernity; Post-modernity; Sociology; Quotidian; ACCNPQ::Ciências Humanas::Sociologia